Kepedulian Sarjana Hadīth Dalam Ilmu Qiraʾat; Tokoh Dan Penulisan - Norazman Alias; Zainora Daud; Anuar Hasin (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BM016 347 - 357